2013
DOI: 10.1007/s10895-013-1166-1
|View full text |Cite
|
Sign up to set email alerts
|

Spectrofluorimetric Determination of Fluoroquinolones in Honey with 2,3-Dichloro-5,6-dicyano-1,4-benzoquinone in the Presence of β-cyclodextrin

Abstract: A simple and sensitive spectrofluorimetric method was developed for the determination of four fluoroquinolone antibacterials namely norfloxacin (NOR), ofloxacin (OFL), ciprofloxacin (CIP) and gatifloxacin (GAT) in honey through charge transfer (CT) complex formation with 2,3-Dichloro-5,6-dicyano-1,4-benzoquinone (DDQ), and then the inclusion complexes of FQs-DDQ with β-cyclodextrin (β-CD) were formed, which resulted in drastic fluorescence enhancement. The effect of several parameters including the concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…As are shown in Table 3, the slope ratios range between 0.86 and 1.11 for the 16 FQs in lotion and cream matrices, indicating that the interfering substances in cosmetic samples were effectively eliminated through the SPE clean-up protocol. 20 …”
Section: Methods Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…As are shown in Table 3, the slope ratios range between 0.86 and 1.11 for the 16 FQs in lotion and cream matrices, indicating that the interfering substances in cosmetic samples were effectively eliminated through the SPE clean-up protocol. 20 …”
Section: Methods Validationmentioning
confidence: 99%
“…The cone voltage and collision energy for each MS/MS transition in the SRM mode were optimized individually and the optimum values are given in Table 1. Data acquisition was performed with multiple channels set 20 based on the retention time of each reference compound. Instrumentation control and data acquisition were operated by MassLynx and TargetLynx software, supplied with the instrument (Waters, Manchester, UK).…”
Section: Uplc-ms/ms Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Blank urine was then tested to ascertain the absence of any endogenous interference at the retention time of GFX and OFX. An eight-point calibration curve (5,15,25,50,150,200, 400 and 500 ng mL −1 ) was constructed by plotting the peak area ratio of GFX to OFX (IS) ( -axis) versus GFX nominal concentrations ( -axis). Analysis of calibration samples at each concentration was performed in triplicates.…”
Section: Sample Preparation Procedures and Construction Of The Calibramentioning
confidence: 99%
“…An extensive literature survey revealed that several analytical methods have been reported for the determination of gemifloxacin in pharmaceutical preparations or human plasma or even in honey. Such methods are the various spectrophotometric techniques [16][17][18][19][20][21][22][23][24][25], capillary electrophoresis [26], high performance liquid chromatography [27][28][29][30][31][32][33][34][35][36], LC-mass spectrometry [37][38][39][40][41], microchip electrophoresis [42], chemiluminescence [43] and potentiometry [44] These methods were related to some major drawbacks such as having inadequate sensitivity, being time-consuming, tedious and sophisticated sample preparation. However, to the best of our knowledge, determination of GFX with complete validation in human urine has never been published.…”
Section: Introductionmentioning
confidence: 99%